Penerapan Kriptografi Md5 Pada Sistem Informasi Penjualan Online Produk Cat Berbasis Web - Darmawan, Muhammad Albani; Karman, Joni; Intan, Bunga (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PT Warna Agung in Palembang is a company engaged in selling paint products. Currently, the sales and marketing process at the company still uses conventional methods. In the digital era that continues to develop, this method is considered less efficient and risks leaving companies behind competitors who are already utilizing technology. In addition, managing sales data manually is often time-consuming and error-prone. Therefore, there is a need for innovation to increase efficiency and security in managing sales data. The main problem faced by PT Warna Agung is limitations in managing sales and marketing effectively in the digital era. In facing increasingly fierce competition, companies must be able to utilize technology to simplify business processes and reach more customers. In addition, data security in digital transactions is very important to protect sensitive company and customer information. The solution offered in this research is the development of a web-based online sales information system equipped with MD5 cryptography to secure data. This system is designed to make it easier to manage sales data digitally, expand the reach of online marketing, and increase the company's operational efficiency. The aim of this research is to provide technology-based solutions that are able to increase efficiency and safety in the product sales and marketing process. The result of this research is an online sales website that can manage data digitally and facilitate online marketing with enhanced security using MD5 cryptography, thereby supporting the sustainability of PT Warna Agung's business in the digital era.